Viability of basidiospores of Agrocybe cylindracea and Oudemansiella mucida and antibiotic activity of monosporic isolates in the course of 15 years of storage - Semerdzieva, M (Folia microbiologica, 1992)
Basidiospores of Agrocybe cylindracea were found to be viable for 12 years, those of Oudemansiella mucida for 6 years. The ability of monosporic isolates from these spores to produce antibiotics has been partly preserved.
Keywords: Spores, Fungal; časové faktory; Time Factors; Basidiomycota; Anti-Bacterial Agents; spory hub; antibakteriální látky